2008
DOI: 10.1016/j.bbabio.2008.04.039
|View full text |Cite
|
Sign up to set email alerts
|

His92 and His110 selectively affect different heme centers of adrenal cytochrome b561

Abstract: Adrenal cytochrome b(561) (cyt b(561)), a transmembrane protein that shuttles reducing equivalents derived from ascorbate, has two heme centers with distinct spectroscopic signals and reactivity towards ascorbate. The His54/His122 and His88/His161 pairs furnish axial ligands for the hemes, but additional amino acid residues contributing to the heme centers have not been identified. A computational model of human cyt b(561) (Bashtovyy, D., Berczi, A., Asard, H., and Pali, T. (2003) Protoplasma 221, 31-40) predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 56 publications
8
40
0
Order By: Relevance
“…As expected from previous results (7, 16) the heme content of wildtype cyt b 561 was almost exactly two per monomer (Supplementary Material, Table S2), showing that most modifications of EM3 sidechains did not prevent incorporation of a full heme complement into the protein. The basic functionality of each recombinant protein was assessed by comparison of the intensity of alpha band absorbance from cytochrome reduction upon addition of 20 mM ascorbate to that upon complete reduction by dithionite (Supplementary Material, Table S2; full spectra of wildtype cytochrome and selected mutants are in Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As expected from previous results (7, 16) the heme content of wildtype cyt b 561 was almost exactly two per monomer (Supplementary Material, Table S2), showing that most modifications of EM3 sidechains did not prevent incorporation of a full heme complement into the protein. The basic functionality of each recombinant protein was assessed by comparison of the intensity of alpha band absorbance from cytochrome reduction upon addition of 20 mM ascorbate to that upon complete reduction by dithionite (Supplementary Material, Table S2; full spectra of wildtype cytochrome and selected mutants are in Fig.…”
Section: Resultssupporting
confidence: 89%
“…Ascorbate titrations were performed as previously published with minor changes (7). Pre-oxidized cyt b 561 samples (5–11 μM) in 100 mM potassium phosphate buffer (pH 7.2) containing 18% glycerol and 0.08% (w/v) n-dodecyl-β-D-maltoside were placed in a 1-cm quartz cuvette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in other conserved and partially conserved residues of mouse CYB561s had variable effects on TMET activity and ASC reduction (34,41,45,54). Consistent with the putative location of the electron-accepting and -donating sides, mutations in loop regions on the intra-vesicular side severely decreased LCytb/CYB561A3 TM Fe 3 + -reductase activity, but mutations on the cytoplasmic side had comparatively less effect (54).…”
Section: Site-directed Mutagenesismentioning
confidence: 70%
“…Western blot analysis and spectroscopy demonstrated that mutation of His residues coordinating the LP-heme (intra-vesicular-side) of Arabidopsis TCytb/ CYB561B1, and mouse CGCytb/CYB561A1, resulted in nearly undetectable protein levels. In contrast, mutations in the HPheme-coordinating residues hardly affected CYB561 expression, but resulted in altered ASC-reduction kinetics and reduced heme content (11,28,34). Somewhat contradicting results were obtained with His mutations in human DCytb/CYB561A2, and need further investigation (37,45).…”
Section: Site-directed Mutagenesismentioning
confidence: 94%